Biochemical Composition of Koi (Anabas testudineus) Collected from Paddy Field of Mymensingh, Bangladesh: Short Communication: Biochemistry of Koi (Anabas testudineus) - Begum, Mohajira; Minar, Maruf Hossain (Biological Sciences - PJSIR, 2014)